Dosage Changes of a Segment at 17p13.1 Lead to Intellectual Disability and Microcephaly as a Result of Complex Genetic Interaction of Multiple Genes - Fonseca, Claudia Marcia Benedetto de Carvalho (2014)
Baylor College of Medicine. Department of Molecular and Human Genetics. Houston, TX, USA /Fundação Oswaldo Cruz. Centro de Pesquisas Rene Rachou. Belo Horizonte, MG, Brazil